?HYDROCHLORIC ACID LEACHING OF MINERALS FROM NIGERIAN SOIL (Biological Sciences - PJSIR, 1999)
Effects of particle size on theleaching of some metals(Mn,Cu,Fe andZn) fromsoil was studied atroom temperature and different hydrochloric acid concentrations. It was found that the metal concentration in the leachate decreases steadily with increasing leaching time up to a limit with exception of iron. However,the metal concentration observed at 75f!m and 288f!m did not differ largely after a long time of leaching. The highest metal concentration was obtained using a particle sizeof75f!m.Alinearrelationshipwasestablishedbetweentheplotsofinverseofconcentration intheleachate and inverse of leaching time.This observationconfirms thevalidity oftheproposed equation for thecorrelation of the concen- tration in theleachate withleaching time. The correlationofthepredictedleachingconcentrations with theexperimentally determined ones showed only 11.0%deviation.